INTERGENERATIONAL INSIGHT OF FRAUD INTENTION IN DIGITAL BANKING: WHAT MAKES CUSTOMERS GO ROGUE? - Ali Maskur; Santoso, Ignatius Hari (Fakultas Ekonomi dan Bisnis Universitas Katolik Indonesia Atma Jaya, 2025)
This study investigates the factors influencing customers' intention to commit fraud in the context of mandatory digital banking, with a focus on intergenerational differences between Generation Y and Millennials. Guided by the Fraud Triangle Theory, the research explores how perceived opportunity, financial pressure, and rationalization contribute to fraud intention. A mixed-method approach was employed, beginning with in-depth qualitative interviews followed by a quantitative survey of 100 digital banking users in Indonesia. The constructions were validated through factor analysis, and the model was tested using Partial Least Squares (PLS-SEM). The findings reveal that perceived opportunity and rationalization significantly influence fraud intention, while financial pressure does not. Furthermore, generational differences do not moderate the relationships between the predictors and fraud intention. These results highlight the importance of improving digital system integrity and addressing ethical rationalizations to prevent fraud. The study contributes to a deeper understanding of consumer-initiated financial fraud in the digital age and suggests avenues for more targeted fraud prevention strategies.